THE EFFECT OF ADOLESCENTS’S PSYCHOLOGICAL STRESS ON THE MENSTRUAL CYCLE IN STUDENTS AT SMK MULIA HATI INSANI WARUNGGUNUNG, LEBAK REGENCY IN 2023 - Suara, Mahyar; Apriliani, Pina (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Based on a preliminary study conducted at SMK Mulia Hati Insani Warunggunung, Lebak Regency, it was found that 80% (16 out of 20) female students experienced menstrual cycle disorders. Purpose: To determine the effect of adolescents’s psychological stress on the menstrual cycle in female students at SMK Mulia Hati Insani Warunggunung, Lebak Regency. Methods: Cross sectional through a point time approach where samples are taken using 20% of the total population, which is as many as 70 respondents. Data analysis using chi square test. Results: Shows psychological stress affects the menstrual cycle (p-value 0.000). Conclusion: There is an affect of adolescents’s psychological stress on the menstrual cycle of female students. It is hoped that students can strengthen coping mechanisms in dealing with stressors when carrying out their duties as students at school and their adolescent life outside school so that the growth and development process becomes optimal and the menstrual cycle becomes regular.